(untitled) (Research, Society and Development, 2021)
The objective of this study was to carry out an economic evaluation of Tambatinga larviculture in three stocking densities (10, 20 and 30 post-larvae / liter) submitted to the biofloc system (BFT) and clear water (AC) using the data zootechnics collected during a 12-day experimental period. Larviculture was designed for the city of Cuiabá-Mato Grosso. The Effective Operating Cost, Total Operating Cost and Total Production Cost (CT) were measured, and the cost-benefit analysis of the BFT and AC systems was performed using the financial-productive indicator (Ifp) (g / R ). The CTs (R / liter) of treatments with BFT were R 0.0843 (10 post-larvae / liter), R 0.134 (20 post-larvae / liter), R 0.1837 (30 post-larvae) / liter), these values ​​being higher than the CTs found in CA of R 0.0588, R 0.1088, R 0.1589, respectively. Ifps, of densities 10, 20 and 30 in BFT, in this order, were 0.287g, 0.1392g and 0.0651g for each R 1.00 of CT. In AC, the Ifps were 0.0639g / R 1.00, 0.0789g / R 1.00 and 0.1052g / R 1.00, as the density increased. Through Ifp, it was possible to assess that even with a higher TC, the use of BFT systems, with a density of 10 and 20 post-larvae / liter, allows greater gain of final biomass for each real allocated in the activity.